2010
DOI: 10.14198/jopha.2010.4.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Children’s relationships with robots: robot is child’s new friend

Abstract: Abstract-The purpose of this study was to examine how children think about and attribute features of friendship to a robot after a brief interaction with one. Children visiting a science centre located in a major Western Canadian city were randomly selected to participate in an experiment set up at the centre. A total of 184 children ages 5 to 16 years (M = 8.18 years) with an approximate even number of boys and girls participated. Children were interviewed after observing a traditional robot, a small 5 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This increased level of engagement may be due to the perception of a more rich interaction and more similar to that among humans, in particular friends, as observed above and supported also in [16], [20], despite the fact that no differences in perception of the robot were measured between the conditions. Another way to investigate the children's engagement is to analyze the length of their interactions with the system.…”
Section: B Interest To Have Further Interaction(s)supporting
confidence: 65%
“…This increased level of engagement may be due to the perception of a more rich interaction and more similar to that among humans, in particular friends, as observed above and supported also in [16], [20], despite the fact that no differences in perception of the robot were measured between the conditions. Another way to investigate the children's engagement is to analyze the length of their interactions with the system.…”
Section: B Interest To Have Further Interaction(s)supporting
confidence: 65%
“…Previous research has shown that children can perceive robots as friends (Fior et al 2010;Hyun et al 2010;Kanda et al 2004;Tanaka et al 2007), although robots are also seen as a separate ontological entity or "hybrid being" (Eunja et al 2012;Kahn et al 2013). Thus, although robots are not perceived to be completely human (Eunja et al 2012), children nevertheless seem to project their understanding of humans onto robots, allowing friendships to form (Beran and Ramirez-Serrano 2011).…”
Section: Developmental Effects On Childrenmentioning
confidence: 99%
“…These robots are known as social robots. Social robots hold a variety of different functions, including aiding the elderly, acting as tour guides, and even tutoring [57,58]. The robots can also have emotional roles, acting as companions, allowing people to cope with negative states such as depression, loneliness, and disability [59].…”
Section: Applicationsmentioning
confidence: 99%
“…Research has shown (perhaps via a naïve biology mechanism), that humans attribute verbal communication to robots if they have mouths. According to one study, the attribution of verbal communication is enough for people to start a conversation with the robot [58].…”
Section: Nao Robotsmentioning
confidence: 99%